Chronicle of currency collapses: re-examining the effects on output - Matthieu Bussière; Sweta C. Saxena; Camilo E. Tovar (European Central Bank (ECB), 2010)
The impact of currency collapses (i.e. large nominal depreciations or devaluations) on real output remains unsettled in the empirical macroeconomic literature. This paper provides new empirical evidence on this relationship using a dataset for 108 emerging and developing economies for the period 1960-2006. We provide estimates of how these episodes affect growth and output trend. Our main finding is that currency collapses are associated with a permanent output loss relative to trend, which is estimated to range between 2% and 6% of GDP. However, we show that such losses tend to materialise before the drop in the value of the currency, which suggests that the costs of a currency crash largely stem from the factors leading to it. Taken on its own (i.e. ceteris paribus) we find that currency collapses tend to have a positive effect on output. More generally, we also find that the likelihood of a positive growth rate in the year of the collapse is over two times more likely than a contraction, and that positive growth rates in the years that follow such episodes are the norm. Finally, we show that the persistence of the crash matters, i.e. one-time events induce exchange rate and output dynamics that differ from consecutive episodes.
Keywords: E32; F31; F41; F43; 330; currency crisis; Exchange Rates; nominal depreciations; nominal devaluations; real output growth; recovery from crises; Währungskrise; Bruttoinlandsprodukt; Abwertung; Schwellenländer; Entwicklungsländer